A study on the control system of electric water heaters for decarbonization - FEYZİOĞLU, AHMET (My University, 2023)
Greenhouse gas (GHG) emissions have significantly increased in recent years as a result of population rise and the increase in the number of residences, with high levels of energy use in homes and household appliances. It is crucial to move the housing industry away from high-carbon sources and toward low-carbon sources in order to minimize greenhouse gas emissions as a precaution. One of the most crucial systems that needs to be provided in order to achieve energy efficiency is the electric water heater (EWH), as they rank among the top electricity consumers. In this study, a double-tank EWH model was developed and simulated at various tank sizes (100 L, 200 L, 300 L and 400 L) and power ratios (1 kW, 2 kW, 3kW and 4 kW) in order to demonstrate energy efficiency. To obtain information for the simulation analysis of the tanks, the hourly water usage of 25 houses was measured. The single-tank and the double-tank models created for this study were both run in the Matlab/Simulink environment with an on-off controller applied, and their energy consumption was compared. Amounts were also determined based on how much energy both tanks consumed. It has been noted that the amount of GHG emissions is also reduced because the double tank uses less energy than the single tank does. The simulation showed that compared to the single tank, the dual tank produced 46.62% less GHG emissions at 45 W power and 47.51% less GHG emissions at 80 W.
Keywords: Makina Mühendisliği; Mühendislik ve Teknoloji; Mechanical Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Physical Sciences; electric water heater simulation; tank control; hot water profile; greenhouse gas emission; decarbonization